Impacts of cation ordering on bandgap dispersion of double perovskites - Kim, Jongseob; Kim, Hyungjun; Chandran, Mahesh; Lee, Seung-Cheol; Im, Sang Hyuk; Hong, Ki-Ha (AMER INST PHYSICS, 2018)
Double perovskites using dual metal cations are promising candidates for Pb-free perovskites. This study shows that the electronic structures of double perovskites (A(2)B(+)B(3+)X(6)) can be significantly modulated by cation ordering changes. The bandgap of Cs2AgBiCl6 can be affected by changing octahedron alignments, and even zero gap states can be realized for the 2-dimensional BiCl6 (AgCl6) configuration. It is presented that different types of B+/B3+-site orderings in double perovskites could be the origin of bandgap dispersion. Comparative studies on the various compositions show that, among B+/B3+ cations, Tl/Bi could be promising for the suppression of ordering variation. (C) 2018 Author(s).
Keywords: HALIDE DOUBLE PEROVSKITES; EFFICIENCY